The role of the integration of the knowledge economy and international accounting in achieving sustainable development - علي محمد ابراهيم (Journal of Economics and Administrative Sciences, 2015)
The current environment is witnessing several developments as a result of the changes taking place in all areas of economic, social , political and legal that led to the transformation of the industrial economy , which depends based on quantitative production to a knowledge economy which relies based on information and knowledge , as the central pillar of this economy during the trading of these information and knowledge between all individuals in general and decision makers , in particular, through information and communication technology of computers and the Internet to achieve sustainable human development in the social dimension. It is known that the decisions of foreign investment depends based on the information the International Accounting (minimum) of the information contained in the consolidated financial statements and information that takes into account the changes in the general price level ( inflation accounting ) and information on income tax in the state , which meant investing in , this means that the information accounting that are offered through the accounting systems of local applicable in each country according to the standards , rules and regulations for each state is unable to provide such information , and thus become useless to the decisions of foreign investment , hence emerged the problem of basic research through the following question : is the information local accounting in each country are useful in making decisions of foreign investment to achieve sustainable economic and social development. Hence the need for an international accounting be able to provide accounting information to meet the needs of decision makers who are in all over the world to make rational decisions , that will contribute to achieving sustainable development in the economic and social dimension.